2021
DOI: 10.1159/000519094
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Macroprolactinemia in Patients with Hyperprolactinemia Using Roche Elecsys Platform in a Large Tertiary Referral Center in UAE

Abstract: <b><i>Objectives:</i></b> Macroprolactin (macroPRL) excess is an important cause of hyperprolactinemia. Several prolactin assays have high reactivity to macroPRL. However, macroPRL screening is not routinely performed in many labs. This study aimed to evaluate the prevalence of macroprolactinemia (MP) in patients with elevated prolactin using the Roche Elecsys assay in a large tertiary center in UAE. <b><i>Materials and Methods:</i></b> Consecutive samples of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Previous studies showed a similar prevalence of macroprolactinemia. 21 , 22 This highlights the need to measure macroprolactin in all patients with hyperprolactinemia to avoid unnecessary interventions. 23 Although patients with macroprolactinemia are usually asymptomatic, some patients may present with symptoms that need to be managed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed a similar prevalence of macroprolactinemia. 21 , 22 This highlights the need to measure macroprolactin in all patients with hyperprolactinemia to avoid unnecessary interventions. 23 Although patients with macroprolactinemia are usually asymptomatic, some patients may present with symptoms that need to be managed.…”
Section: Discussionmentioning
confidence: 99%
“…Macroprolactinemiua has been reported in up to 40% of all patients with hyperprolactinemia without symptoms. 11 12 On the contrary, pregnancy is a physiologic cause of significant prolactin elevation that must be excluded in young females with hyperprolactinemia. Renal and liver impairment may elevate the prolactin due to subnormal prolactin elimination from the circulation.…”
Section: Diagnostic Evaluationmentioning
confidence: 99%